2013
DOI: 10.30970/cma6.0270
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure changes in the Ni3Ta intermetallic compound

Abstract: The crystal structure changes in Ni 3 Ta were experimentally investigated by X-ray powder diffraction of alloys prepared by arc melting, ground and annealed in the temperature range 673-1173 K for 1 day. It was found that an increase of the annealing temperatures leads to a change of the product of the transformation of the high-temperature tetragonal phase from monoclinic to orthorhombic. The changes are promoted by recovery and recrystallization processes. Some oxidation at the higher annealing temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…However, XRD pattern of NiTa-1000 sample also includes peak positions of the all phases are also in accordance with the literature [7,8,15,16] and the corresponding phases are marked on patterns. Also, as expected, all samples contained austenite phase at room temperature [11,13,17]. The XRD pattern of NiTa-0 sample display in Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, XRD pattern of NiTa-1000 sample also includes peak positions of the all phases are also in accordance with the literature [7,8,15,16] and the corresponding phases are marked on patterns. Also, as expected, all samples contained austenite phase at room temperature [11,13,17]. The XRD pattern of NiTa-0 sample display in Fig.…”
Section: Resultssupporting
confidence: 80%
“…Ni3Ta. Likewise, Kosorukova et al [13] reported that as aging temperature increased the stable orthorhombic Ni3Ta phase was formed in the Ni3Ta alloy, as a result of diffusional phase transformation mechanism. Consequently, the results indicated that heat treatment performed at 1000 o C led to starts diffusional phase transformation in the Ni-25.5Ta (at.%) alloy.…”
Section: Resultsmentioning
confidence: 93%
“…The Ni-Ta binary system has been investigated by many researchers [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In 2018, Zhou et al [30] reviewed the Ni-Ta system, where only four intermetallic compounds Ni 2 Ta, Ni 3 Ta, NiTa, NiTa 2 , and two terminal solid solutions fcc-(Ni), bcc-(Ta) coexisted, and the Ni 8 Ta was confirmed to be a metastable phase.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, among many high temperature SMAs, the Ni-Ta alloy has increasing interest and its structural and morphological properties, martensitic transformation behaviour and shape memory effect has been studied depending on its composition [11], by adding third alloying elements [9,10] and under predeformed states [7,8]. However, the Ni-Ta alloy system has some disadvantages: cracks in microstructure [7] and tetragonal austenite phase at room temperature with high volume fraction [13]. It has been seen that the crack problems in the Ni-Ta alloy could be tackled with changing homogenization conditions [11].…”
Section: The Research Findings and Discussionmentioning
confidence: 99%